Die zerstörerische Schöpfung: Kapitalistische Entwicklung zwischen Zivilisierung und Entzivilisierung - Altvater, Elmar (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
Starting with Marx’s considerations about the double nature of capitalist development as bringing forward civilization and at the same time undermining civilization, recent developments of capitalism are discussed. Destructive forms of “primitive accumulation” and “accumulation by dispossession” are not elements of a past period of capitalism, they are always present. By disembedding markets from social regulations, instead of the Schumpterian process of “creative destruction”, a dangerous process of “destructive creation” is accelerated, which can only be stopped by opposite social movements.